(untitled) (Al-Academy, 2016)
This research is marked by " lighting and processors formalism for spaces of shops selling mobile phones ," aims to " reveal about the relationship between lighting treatments formal designs spaces own internal selling mobile phone in addition to the recognition criteria Altsamama to lighting techniques and processes formality spaces shops competent to sell mobile phone " and lies the importance of this research in the " active role of the lighting in the building processors formalities and processes to prepare designs and show the final form integrated functionally and aesthetically so as to be ready for implementation , taking into consideration the role expressionist in the recipient and to make these spaces more than meet the requirements of Alasralhaddat being spaces of a private sale of mobile devices , which Aattabrahadd types Alknlogia digital in the current century , " in order to achieve the objectives of the research , the researcher draw axes analysis of indicators has included the following points :1 - Achieve digital computer techniques and lighting effects in spaces of selling fake mobile phones, laser techniques different types and optical fibers .2 - achieving racial thrills and attractions in the width of the spaces through the use of digital computer techniques for lighting on the level and means of the external display , internal display modes , and determinants of vertical and horizontal .3 - To achieve visual comfort in the space of maintenance through study variables lighting and factored angle of the fall of light , reflection coefficient of the work surface , the intensity of light , color lighting , type of lighting , and high Musdraldu .4 - to achieve balance digital lighting technologies in the space of visual display on the sale of the mobile phone through the study of the relationship between them and the visual elements Kvh , color , texture , size, and location.This has included the research community on the spaces selling mobile phones in the city of Baghdad , as it chose a researcher from the research community Rusafa in the city of Baghdad and the rate of ( 7) and administrative units adopted researcher sample Alhssah class were identified and two units represented (28.5 %) of the administrative units and represented by ( 80 replaces Mobile), was also selected (20 %) of those units represented by four spaces sale of mobile phones in by Rusafa Vdaúan the them in the new Baghdad district (Street Rubaie ) and Vdaúan of the other people in the neighborhood banks . The analysis process resulted in the development of a set of conclusions :1 - affect the change in systems and optical properties of formations to achieve the optical illusion in the spaces of immunity and selling mobile phones and of the lighting techniques used and methods of use .2 - increasingly feeling Paljzb and enjoy the internal spaces of the sale of the mobile phone when you use colored lighting techniques at the interface and within the space , which gives the aesthetic image of an integrated attractive and comfortable and enjoyable.3 - that the proper distribution of the lighting units , ceiling and wall height and angle study the fall of the light rays have a significant role in achieving visual comfort to the customer in the width of the space together and achieve visual comfort in the space of maintenance from the other side .4 - need varying the intensity of light according to the space - effectiveness requirements as per the effectiveness of a certain level of severity Lighting , where the nature of the spaces in a manner determined by the sensory response resulting from varying the intensity of light and understood by the receiver through.5 - the need to achieve balance through visual examination of the relationship between the light and the optical elements of the severity of color and texture in both display modes or in the determinants of vertical and horizontal .6 - There is a lack of interior designer and technical abilities in the preparation of formal processors , it seems clear from the lack of visual elements and design relationships in selling mobile phones spaces